2018
DOI: 10.1002/wps.20514
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the “at risk mental state” concept: transitioning to transdiagnostic psychiatry

Abstract: The "at risk mental state" for psychosis approach has been a catalytic, highly productive research paradigm over the last 25 years. In this paper we review that paradigm and summarize its key lessons, which include the valence of this phenotype for future psychosis outcomes, but also for comorbid, persistent or incident non-psychotic disorders; and the evidence that onset of psychotic disorder can at least be delayed in ultra high risk (UHR) patients, and that some full-threshold psychotic disorder may emerge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
319
1
9

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 375 publications
(343 citation statements)
references
References 91 publications
14
319
1
9
Order By: Relevance
“…What are, or may be, in fact the main elements of that second step? They include the characterization of the individual case with respect to the relevant psychopathological dimensions and possibly to the current stage of development of the diagnosed disorder (see McGorry et al in this issue of the journal); an assessment of the severity of the clinical picture which is less generic and more evidence‐based than that currently provided by the ICD and the DSM; the exploration of antecedent variables such as family history of mental illness, other parental factors, perinatal factors, early environmental exposures, psychomotor development, premorbid social adjustment, psychopathological antecedents, and possibly in the future polygenic risk scores; and the assessment of concomitant variables such as personality traits, cognitive functioning, social functioning (including personal resources such as resilience and coping strategies), soft neurological signs, substance abuse, recent environmental exposures, and possibly in the future some biological markers. It is with respect to the assessment of these latter elements that clinicians need today a systematic guidance, which current diagnostic systems and related tools do not provide, or do not provide satisfactorily (thus contributing to a therapeutic practice which, being guided just by a diagnostic label, is oversimplified and stereotyped).…”
supporting
confidence: 53%
“…What are, or may be, in fact the main elements of that second step? They include the characterization of the individual case with respect to the relevant psychopathological dimensions and possibly to the current stage of development of the diagnosed disorder (see McGorry et al in this issue of the journal); an assessment of the severity of the clinical picture which is less generic and more evidence‐based than that currently provided by the ICD and the DSM; the exploration of antecedent variables such as family history of mental illness, other parental factors, perinatal factors, early environmental exposures, psychomotor development, premorbid social adjustment, psychopathological antecedents, and possibly in the future polygenic risk scores; and the assessment of concomitant variables such as personality traits, cognitive functioning, social functioning (including personal resources such as resilience and coping strategies), soft neurological signs, substance abuse, recent environmental exposures, and possibly in the future some biological markers. It is with respect to the assessment of these latter elements that clinicians need today a systematic guidance, which current diagnostic systems and related tools do not provide, or do not provide satisfactorily (thus contributing to a therapeutic practice which, being guided just by a diagnostic label, is oversimplified and stereotyped).…”
supporting
confidence: 53%
“…A recent retrospective investigation of electronic health records data from South East London showed that 16.3% of the patients presented to mental health services with a first-episode psychotic disorder (FEP) had a prior contact with local prodromal services,9 similar to recently disclosed data from Melbourne 10. However, only 4.1% met criteria for UHR/CHR and consequently ‘transitioned’, while the remaining 12.3% had already been diagnosed with FEP at initial contact with prodromal services 9.…”
Section: What Is the Cost-effectiveness Of Special Services For Uhr/chr?mentioning
confidence: 79%
“…In this regard, we believe that the field, after two decades of clinical research, should at least be open for discussion of concerns over the UHR/CHR programme in the light of data. In fact, it is encouraging to see that even the prime movers of the traditional UHR/CHR paradigm move beyond a narrow framework and adopt a broader prevention strategy acknowledging pluripotency 10. Also, instead of the pragmatic surrogate outcome of ‘transition’, higher-level outcomes such as functioning and quality of life may serve as more clinically relevant and service-user-centred outcomes for measuring effectiveness of the early intervention programmes.…”
Section: Resultsmentioning
confidence: 99%
“…In young adults, Fonseca‐Pedrero et al () found that the “High schizotypy” class scored higher on mental distress, hypomanic experiences and anticipatory and consummatory pleasure relative to non‐risk latent classes. It is relevant to note that those subgroups of participants potentially at high risk for psychosis, plus suicide ideation, affective symptoms and/or distressing PLEs may require attention; for instance, could benefit from further comprehensive assessments (eg, clinical interview) in order to analyse their mental health status and developmental trajectories as well as to implement prophylactic preventive interventions (Arango et al, ; McGorry, Hartmann, Spooner, & Nelson, ). It would be particularly relevant to detect those adolescents at risk of suicide behaviour, due to the personal, clinical, and societal implications involved.…”
Section: Discussionmentioning
confidence: 99%